Immunopharmacology of post-myocardial infarction and heart failure medications - Sattler,S; Ng,FS; Panahi,M (Journal of Clinical Medicine, 2018)
The immune system responds to acute tissue damage after myocardial infarction (MI) and orchestrates healing and recovery of the heart. However, excessive inflammation may lead to additional tissue damage and fibrosis and exacerbate subsequent functional impairment, leading to heart failure. The appreciation of the immune system as a crucial factor after MI has led to a surge of clinical trials investigating the potential benefits of immunomodulatory agents previously used in hyper-inflammatory conditions, such as autoimmune disease. While the major goal of routine post-MI pharmacotherapy is to support heart function by ensuring appropriate blood pressure and cardiac output to meet the demands of the body, several drug classes also affect a range of immunological pathways and modulate the post-MI immune response, which is crucial to take into account when designing future immunomodulatory trials. This review outlines how routine post-MI pharmacotherapy affects the immune response and may thus influence post-MI outcomes and development towards heart failure. Current key drug classes are discussed, including platelet inhibitors, statins, β-blockers, and renin–angiotensin–aldosterone inhibitors.